Taxonomic resolution of the hillstream suck-loach Beaufortia pingi species group (Cypriniformes, Gastromyzontidae) and two new species from Southwest China– Beaufortia granulopinna and Beaufortia viridis - Jing-Chen Chen; Jia-Jia Li; Wen-Qiao Tang; Xin-Rui Pu; Hao-Tian Lei (Zoosystematics and Evolution, 2024)
Two new species, Beaufortia granulopinna and Beaufortia viridis, are described from the upper Pearl River system in southwest China. Both species share the characteristics of the Beaufortia pingi species group, including prominent vertical stripes on the lateral body and pinnate-type lower lips, distinguishing them from other Beaufortia species. Beaufortia granulopinna is differentiated from other species in the group by possessing a unique set of characteristics: the presence of well-developed prominent tubercles on the first 6–9 pectoral fin rays in adults; and a significant proportion (54.76%) of individuals experiencing blurriness or absence of vertical stripes in the mid-section of the lateral body upon reaching adulthood. The minimum interspecific genetic distance within the genus based on mitochondrial cytb gene sequences is 10.80%. Beaufortia viridis is distinguished from other species in the group by consistently exhibiting vertical stripes of uniform length, width, and spacing across all stages of growth; the absence of tubercles on the branched rays of pectoral fins; and a body coloration of dark cyan to green. The minimum interspecific genetic distance within the genus based on mitochondrial cytb gene sequences is 4.60%. Molecular phylogenetic results confirm that the Beaufortia pingi species group forms a monophyletic clade, which is congruent with morphological classification findings. This study also addresses and resolves the taxonomic ambiguity surrounding Beaufortia pingi and Beaufortia zebroida, providing a redescription of these taxa.